Public management reform : a comparative analysis - Pollitt, Christopher (OUP E-Books., 2000)
In this major new contribution to a rapidly expanding field, the authors offer an integrated analysis of the wave of management reforms which have swept through so many countries in the last twenty years. The reform trajectories of ten countries are compared, and key differences of approach discussed. Unlike some previous works, this volume affords balanced coverage to the 'New Public Management' (NPM) and the 'non-NPM' or 'reluctant NPM' countries, since it covers Australia, Canada, Finland, France, Germany, the Netherlands, New Zealand, Sweden, the UK and the USA. Unusually, it also includes a preliminary analysis of attempts to improve management within the European Commission.